Journal of the Pali Text Society. Volumes XIX-XXI. - Norman, K. R. (Buddhist Studies Review, 1997)
Journal of the Pali Text Society. Volumes XIX-XXI, Pali Text Society, Oxford 1993, 1994, 1995. £17.25 each.